KINERJA PENGELOLAAN PENGADUAN PELAYANAN PADA BADAN PENANAMAN MODAL DAN PERIZINAN (BPMP) KOTA SURAKARTA - -, Suwardi (Transformasi, 2014)
Act 25 of 2009 on public service requires a complaints management unit. Board of Investmentand Licensing Surakarta put service complaints as an important part of community service.Although not optimally managing complaints have been going well. Along with the changes intheir relationship with the state mainset, complaint management required to keep clean.Keywords: Service; public; complaint; licensing